2013
DOI: 10.1016/j.cemconcomp.2012.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Self-healing capability of cementitious composites incorporating different supplementary cementitious materials

Abstract: a b s t r a c tThe presence of deleterious substances and their transport are among the most important factors controlling the durability of cementitious composites. The present paper studies the relationship among the applied mechanical deterioration in terms of splitting tensile deformation, curing conditions and chloride ion permeability of Engineered Cementitious Composites (ECCs) that contain different supplementary cementitious materials (SCMs). Three SCMs, representing a wide range of compositions, were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
99
0
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 284 publications
(119 citation statements)
references
References 16 publications
(18 reference statements)
7
99
0
3
Order By: Relevance
“…The self-healing performance of the ECC_S mixtures was surprising since it was presumed that specimens with slag would result in considerably lower amounts of anhydrous materials and higher matrix maturity along with higher total crack openings upon pre-loading. The enhanced self-healing performance of microcracked ECC_S specimens has been of issue in another study of the authors of this paper (Sahmaran et al 2013). In that study, the authors concluded that since slag particles have lower amounts of SiO 2 in their chemical compositions compared to other mineral admixtures, lower rates of pozzolanic reactions are anticipated, which would cause portlandite (as a product of cement hydration) to remain longer and in greater amounts in the cementitious matrices, leading to higher pH of the pore solution.…”
Section: Effects Of Self-healingmentioning
confidence: 99%
See 1 more Smart Citation
“…The self-healing performance of the ECC_S mixtures was surprising since it was presumed that specimens with slag would result in considerably lower amounts of anhydrous materials and higher matrix maturity along with higher total crack openings upon pre-loading. The enhanced self-healing performance of microcracked ECC_S specimens has been of issue in another study of the authors of this paper (Sahmaran et al 2013). In that study, the authors concluded that since slag particles have lower amounts of SiO 2 in their chemical compositions compared to other mineral admixtures, lower rates of pozzolanic reactions are anticipated, which would cause portlandite (as a product of cement hydration) to remain longer and in greater amounts in the cementitious matrices, leading to higher pH of the pore solution.…”
Section: Effects Of Self-healingmentioning
confidence: 99%
“…Just as in the sorptivity measurements, tests were repeated after 7, 30, 60 and 90 days of CW exposure beyond initial curing periods to observe selfhealing performance of ECCs. Although different crack characteristics were acquired with the application of pre-loading to ECCs with different mineral admixtures (MAs), the effect of self-healing on crack recoveries has not been accounted for in this study since this point has already been investigated in detail in several previous papers (Sahmaran et al 2013(Sahmaran et al , 2014.…”
Section: Experimental Programmentioning
confidence: 99%
“…Among the major technical strategies for developing self-healing cements, autogenous healing relies on the hydration of residual non-hydrated and partially hydrated cement particles by permeation of water through cracks and the carbonation of hydrates with crack plugging by the hydration and carbonation reaction products (Edvardsen, 1999;Huang et al, 2013;Talaiekhozan et al, 2014). Another, autogenous healing approach involves the incorporation of pozzolan-latent cementitious materials such as fly ash (Sahmaran et al, 2008(Sahmaran et al, , 2013Termkhajornkit et al, 2009), ground granulated blast-furnace slag (GBFS) (Huang et al, 2014) and silica fume (Qian et al, 2010) as healing aids into cements. In contact with calcium-and sodium-containing alkaline fluids penetrating through the fractures, these nonreacted pozzolan materials form amorphous and crystalline calcium silicate, calcium aluminosilicate, sodium aluminosilicate and calcium(sodium) aluminosilicate products, which seal the cracks.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, water does not only promote further hydration of cement and binder grains but may also encourage the dissolution and leaching of calcium hydroxide from the cementitious matrix to form calcium carbonate self-healing crystals with the carbon dioxide dissolved in water [7]. Different supplementary cementitious materials, such as fly ash (class C or F) and slag, also play different role in enhancing the self-healing capacity [8], thanks to their delayed reaction, guaranteeing the repeatability and persistence of the same capacity upon repeated cracking-healing cycles [9].…”
Section: Introductionmentioning
confidence: 99%